2020
DOI: 10.1002/psp.2317
|View full text |Cite
|
Sign up to set email alerts
|

Ageing strategically: On migration, care, and diversity in later life

Abstract: This paper discusses how different groups of older migrants originating in the Global North and Global South converge in the Portuguese islands of the Azores-a microcosm of global migration and a site of inscribed healthcare inequalities-where they strategically maximise the economic and social capital accumulated over the life course to achieve a better life (style). Drawing on the concepts of "strategic switching" and "geographic arbitrage," the paper extends these debates to the domains of ageing and care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, older people and/or people with health problems experience more insecurity in the degree of preparedness, as they need to ensure that they will have access to health and social services on their return. 44…”
Section: Intermediary Determinantsmentioning
confidence: 99%
“…Furthermore, older people and/or people with health problems experience more insecurity in the degree of preparedness, as they need to ensure that they will have access to health and social services on their return. 44…”
Section: Intermediary Determinantsmentioning
confidence: 99%
“…It was recently suggested that manoeuvring through different locations, later-life migrants consider structural opportunities from meso-and macro-levels to improve their quality of life and/or excel in vulnerabilities (Sampaio, 2020;Ciobanu et al, 2017), highlighting their agency in doing so. Concerning social protection drivers, older migrants were studied in the context of their cross-border roles as informal caregivers and care receivers in their transnational families (King et al, 2017;Zickgraf, 2017), their retirement lifestyles, including those seeking to spend their pension abroad generally with better climate conditions and where their pension would have a higher purchasing power (Olsson & O´Reilly, 2017;Croucher, 2012;Gustafson, 2008).…”
Section: A Social Protection and Life-course Take On Older Migrant Im...mentioning
confidence: 99%
“…Migrant minorities often rely on religious communities to create a sense of home in a foreign land, to fill gaps in available social services, to access social networks for employment, and to provide a communal space within which cultural practices and ethnic identities can be passed on to the next generation (e.g. Ebaugh & Chafetz, 2000; Mazumdar & Mazumdar, 2009; Sampaio, 2020; Vásquez & Knott, 2014). Religion is important for the production of diasporic identities in everyday spaces, including households and communities (Vásquez, 2020; Vásquez & Knott, 2014).…”
Section: Digital Articulations Religious Network and Older Adultsmentioning
confidence: 99%
“…In this paper, we draw on two strands of existing transnational research, transnational religion and transnational family scholarship, to examine these crossroads of faith, ageing, migration, and digital media. A growing body of research on transnational religion (Ebaugh & Chafetz, 2000; Khosravi, 2010; Mazumdar & Mazumdar, 2009; Valentine et al., 2013; Vásquez & Knott, 2014) emphasizes the role of digital tools in both connecting migrants to places of worship around the world (Habarakada & Shin, 2018; Vásquez, 2020), and also creating new opportunities to plan for the next life (Sampaio, 2020). However, given the relative exclusion of older adults from discussions on technological narratives, it is in the transnational family scholarship where the role of digital media in ageing lives has been a central thread of inquiry, examined through lenses of ageing, digital media use, migration, and mobility (Ahmed, 2014; Cabalquinto, 2022; Ho, 2014; Madianou & Miller, 2012; Merla & Baldassar, 2010; Ponzanesi, 2020; Sinanan & Hjorth, 2018 ; Wilding et al., 2022), including our previous research that focused on affect and emotions (Baldassar & Wilding, 2020; Wilding, 2018; Wilding et al, 2020).…”
Section: Introductionmentioning
confidence: 99%